AKUNTABILITAS PROGRAM BANTUAN LANGSUNG TUNAI DALAM DANA DESA SUMERTA KAUH TAHUN 2020 PADA MASA PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) (CITIZEN CHARTER, 2022)
Job and government strategy gave BLT-Funds to help individuals impacted by pandemic Responsibility is required as a type of responsibility for the town government in dealing with these assets. One of the towns whose responsibility can be noticed is Sumerta Kauh Village, which is situated in East Denpasar District, Denpasar City. This study expects to examine the impact of introducing a responsibility report on the responsibility of BLT-Dana Sumerta Kauh Village the executives in 2020. The exploration technique utilized in this study was graphic subjective. Information were gathered by perception, interview and documentation strategies. The examination utilizes the hypothesis of accomplishment as per the idea of responsibility in view of the assessment of Jay M. Shafritz and E.W Russel (1977:368) which can be estimated by markers, specifically; The most common way of settling on a choice that is made recorded as a hard copy, accessible to occupants and fulfilling relevant regulatory guidelines gets ideal outcomes, both The precision and culmination of data connecting with ways of accomplishing the objectives of a program has been very much shown by the Sumerta Kauh Village Government. From the goals to be accomplished, a few assessments are required, the fourth is the practicality and consistency of the functional focuses on, the five administration data frameworks and observing of results have been completed ideally. The consequences of the review expressed that the introduction of a responsibility report was expected to make the progress of a program.. Keywords: Village, Assistance, Accountability